1984
DOI: 10.1007/bf00236222
|View full text |Cite
|
Sign up to set email alerts
|

The thalamo-caudate versus thalamo-cortical projections as studied in the cat with fluorescent retrograde double labeling

Abstract: The distribution of thalamic cells projecting to the head of the caudate and their interrelations with thalamo-cortical cells were studied in the cat with different combinations of fluorescent tracers. Injections in the head of the caudate were combined with the injections in the pericruciate, proreal, suprasylvian, anterior cingulate, occipital and ectosylvian cortices. The following results were obtained: (i) Injections in the head of the caudate resulted in retrograde labeling of thalamic cells medially and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(48 citation statements)
references
References 31 publications
3
45
0
Order By: Relevance
“…For these reasons, we cautiously suggested that these deactivations might re¯ect the eects of frontal and thalamic activity on the basal ganglia (Maquet et al 1997). Frontal cortex (Selemon and Goldman-Rakic 1985) and intralaminar thalamic nuclei (Macchi et al 1984;Sadikot et al 1990) represent the major sources of aerents to basal ganglia. They are also among the most deactivated brain areas (see related discussions).…”
Section: Slow-wave Sleepmentioning
confidence: 99%
“…For these reasons, we cautiously suggested that these deactivations might re¯ect the eects of frontal and thalamic activity on the basal ganglia (Maquet et al 1997). Frontal cortex (Selemon and Goldman-Rakic 1985) and intralaminar thalamic nuclei (Macchi et al 1984;Sadikot et al 1990) represent the major sources of aerents to basal ganglia. They are also among the most deactivated brain areas (see related discussions).…”
Section: Slow-wave Sleepmentioning
confidence: 99%
“…These projections to the striatum were confirmed by means of more modern tracing techniques, and additional thalamic projections have been also demonstrated. Thus, projections from the midline thalamic nuclei (paraventricular, paratenial, rhomboid and reuniens nuclei), the mediodorsal nucleus, the rostral nuclei of the ventral group and occasional projections from the lateral and posterior thalamic groups have been reported (Jones and Leavitt, 1974;Nauta et al, 1974;Royce, 1978;Sato et al, 1979;van der Kooy, 1979;Veening et al, 1980;Beckstead, 1984a,b;Macchi et al, 1984;Jayaraman, 1985;Philipson and Griffiths, 1985;Smith and Parent, 1986;Berendse and Groenewegen, 1990;Nakano et al, 1990;Giménez-Amaya et al, 1995;de las Heras et al, 1997de las Heras et al, , 1998ade las Heras et al, ,b, 1999.…”
Section: The Thalamostriatal Projectionsmentioning
confidence: 99%
“…Second, we also do not know whether they are collateral fibers of those connecting with thalamocortical neurons. Although there has been some controversy regarding this point (Steriade and Glenn 1982;Royce 1983;Macchi et al 1984;Cesaro et al 1985), there is a growing body of evidence that suggests that thalamostriatal neurons send collaterals to the cortex. Anterograde and retrograde studies in the rat have found some neurons in the PF, and PV thalamic nuclei send collaterals to the cortex as well as to various components of the basal ganglia (Deschênes et al 1996;Otake and Nakamura 1998).…”
Section: Thalamic Territories Of Overlapmentioning
confidence: 99%